1992
DOI: 10.1159/000108981
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Glycerol Treatment of Acute Stroke – A Statistical Review

Abstract: A major cause of death in acute stroke is postinfarction edema. Glycerol is a hyperosmolar agent that is claimed to reduce edema and improve cerebral blood flow and metabolism. Intravenous glycerol therapy has been tested in 8 controlled, randomized trials including 603 patients but with conflicting results. Of 7 studies, the results of the effect of glycerol therapy on death within the first 3 weeks after infarction were combined in a statistical review. Statistical analysis indicated a significant positive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…If we compare this review with the previous one [3], 3 further studies were considered, but still the number of identified trials of glycerol treatment for acute stroke and the total number of patients included were low. The method of randomisation and concealment were adequate in less than half of the trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If we compare this review with the previous one [3], 3 further studies were considered, but still the number of identified trials of glycerol treatment for acute stroke and the total number of patients included were low. The method of randomisation and concealment were adequate in less than half of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted to hospital with acute stroke are also at high risk of dying; the observed one month case fatality rate in trials with placebo treatment varies from 21 to 50 % [3]. Stroke-related oedema is maximal two to four days after stroke onset and is a major cause of early neurological deterioration and death [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 2 recent systematic reviews have not demonstrated any significant effect on stroke mortality [26,27] although there was a tendency towards improved outcome in the treated group. However, 2 recent systematic reviews have not demonstrated any significant effect on stroke mortality [26,27] although there was a tendency towards improved outcome in the treated group.…”
Section: Glycerolmentioning
confidence: 93%
“…Among these are over 200 truly randomised studies whose results have been reviewed recently. [1][2][3][4][5][6][7][8] It is well beyond the resources of a single physician to undertake a systematic review of such a large body of evidence, yet a systematic review is the only means of deriving a useful summary of the evidence. Although the number of trials in other areas of neurology and neurosurgery is perhaps not so daunting, it is safe to assume that most clinical neurologists and neurosurgeons would welcome systematic reviews of all the available evidence from trials, particularly if the review were regularly updated in the light of any new evidence.…”
mentioning
confidence: 99%